PENERAPAN UNSUR PASAL 2 AYAT (1) UNDANG-UNDANG NOMOR 21 TAHUN 2007 TENTANG TINDAK PIDANA PERDAGANGAN ORANG PADA PENYIDIKAN DIUNIT PPA SATRESKRIM POLRES BUKITTINGGI - Rahmad Natun (UNES Journal of Swara Justisia, 2018)
The Bukittinggi Regional Police PPA Satreskrim Unit has received the Policereport No: LP / 07 / A / I / 2018 / SPKT / Res-Bkt, dated January 8, 2018, concerningcases suspected of being criminal acts of Trafficking in Persons. Where there has been asuspicion of a criminal offense "Ordering to do or participate in economic and / or sexualexploitation and / or criminal acts of Trafficking in Persons, as referred to in Article 2Paragraph (1) of Act Number 21 of 2007 concerning Eradication of Crime in Traffickingin Persons. This research is a descriptive analytical study. As for the results of research inthe Application of Elements Article 2 Paragraph (1) of Law Number 21 of 2007 concerningCrime of Trafficking in Persons by Unit Investigators Unit of PPA Satreskrim Bukittinggican be seen from the facts of arrest, witness statements and statements of suspects andapplication of elements of Article that is. The obstacle encountered by Bukittinggi RegionalPolice PPA Satreskrim Unit investigators in investigating criminal acts of Trafficking inPersons is an internal factor originating from a lack of understanding of personnel orinvestigators in carrying out an investigation process of the TPPO Law, in not all TPPOLaw elements can be fulfilled.